Edukacja aksjologiczna na lekcjach polskiego w szkole podstawowej - Jedliński, Ryszard (Dydaktyka Polonistyczna, 2018)
The article presents selected issues regarding axiological education at Polish lessons in IV–VIII grades of primary school. Such education is related to both the way students communicate with the world of values, and evaluation processes which are ingrained in works of literature and various cultural texts, as well as the matters regarding proper understanding of linguistic phenomena overned by expression of axiological content. Lessons at school should include axiological communication based mainly on a dialogue between the teacher and students, which facilitates mutual stimulation of both in the atmosphere of freedom, respect, tolerance and kindness. The article highlights the issue of patriotism, which is important in terms of culture and society, and at the same time essential in terms of educational aims. Patriotism and its different faces were described as part of modern multiculturalism, which demands tolerant behaviour towards “aliens”. Nowadays, we can notice the need to combine patriotic tradition with the new model of patriotism that opens itself to European and global values.